Market Share, Market Value and Innovation in a Panel of British Manufacturing Firms - Blundell, Richard; Griffiths, Rachel; Van Reenen, John (Review of Economic Studies, 1999)
This paper examines the empirical relationship between technological innovations, market share and stock market value. New developments in the estimation of dynamic count data models are used to control for unobserved firm specific heterogeneity. We find a robust and positive effect of market share on observable headcounts of innovations and patents although increased product market competition in the industry tends to stimulate innovative activity. Furthermore, the impact of innovation on market value is larger for firms with higher market shares. We argue that our results are consistent with models where high market share firms have incentives to pre-emptively innovate.